A Rare Case of Giant Mesenteric Lipoblastoma in a 6-Year-Old Child and Review of the Literature - Maria Enrica Miscia; Gabriele Lisi; Giuseppe Lauriti; Angela Riccio; Dacia Di Renzo; Valentina Cascini; Pierluigi Lelli Chiesa (Case Reports in Surgery)
Giant mesenteric lipoblastoma is a rare benign tumor arising from the adipocytes. It can mimic malignant tumors, and its diagnosis is difficult before surgery. Imaging studies could lead the diagnosis but not confirm it. Those tumors arising in the abdomen are usually larger and can cause symptoms of compression. Surgical excision is the treatment of choice, and a long-term follow-up is necessary to detect local recurrences. Only a few cases of lipoblastomas arising from the mesentery are reported in literature. We present a case of a rare giant lipoblastoma arising from the mesentery of a 6-year-old girl, with a history of postprandial abdominal pain.